PERANAN MASYARAKAT TERHADAP PENCEGAHAN KEJAHATAN INCEST BERDASARKAN TEORI KONTROL SOSIAL - Ferawati Royani; Widya Timur (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2021)
Abstract:Criminal law policy regulates incest crime, crime is a social phenomenon that develops in society since ancient times until now. The crime of incest is a sexual relationship committed by two people who are still in a relationship or related relationship or marriage. The legal research method used is normative-empirical is basically a combination of normative legal approaches with the addition of various empirical elements. Incest crime, a crime that often occurs but many are not published by the public. Here the researcher states that incest crime requires an important role from the community using social control theory. Control theory refers to every perspective that addresses the control of human behavior, the object (target) of social control. Seen from the many incest cases, it turns out that the community or family members of victims of incest crimes still do not want or are afraid to report this crime because they feel ashamed / disgrace so that this crime is not entirely prosecuted. In the theory of social control also requires an understanding or socialization of the law against incest.Keywords: control; social; Policy; law